Penerapan Model Kooperatif Tipe TS-TS Melalui Whatsapp untuk Meningkatkan Hasil Belajar pada Mata Kuliah Struktur Aljabar - Ofirenty E Nubatonis (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2020)
This study aims to describe the using cooperative learning TS-TS model on student learning outcomes in the Algebra Structure course. This research is an experimental research using a control class and an experimental class with a pretest posttest control group design. Sampling technique using strata sampling. The number of students in the experimental class was 27 people and the number of students in the control class was 28 people. The data analysis used descriptive N-Gain statistics, normality test, homogeneity test and hypothesis testing with independent t-test. The research data showed that the average post-test score in the control class was 74.47, which was higher than the average learning outcome for the control class, which was 63.46. This shows that the TS-TS type cooperative model is better than the conventional model.